Representations of Istanbul at the Intersection of Modern Turkish Literature and World Literature - TURAN, AYŞEGÜL (Springer, 2023)
As the cultural capital of both the Ottoman Empire and Republic of Turkey, Istanbul has assumed a central role in the literary imagination of the cultural legacy of the imperial past and the modern nation-state. When we consider Turkish literary history, construction of a national literary tradition reveals a close engagement with the West and Western modernity, often resulting in epistemological and ontological questions about the self searching for their place in the world. If Istanbul serves as the main ground for mapping out the anxieties about the national culture, it also provides the opportunity to reach beyond the national boundaries with its multi-layered and cosmopolitan past. In this paper, I contend that Istanbul, for several authors from Turkey, emerges as an important novelistic element and character so much so that it, on the one hand, enables them to discuss the possibilities and limits of the national literature and on the other hand becomes a venue for recognition as part of world literary studies. In this paper, I focus on three novels by three internationally acclaimed authors from Turkey, namely Ahmet Hamdi Tanpinar, Orhan Pamuk and Burhan Sonmez, so as to examine the spatial representation of Istanbul at the intersection of national and world literature. The novels under examination here, A Mind at Peace by Tanpinar (1949, 2008 English translation), The Black Book by Pamuk (1990, 1994;2006 English translation) and Istanbul Istanbul by Sonmez (2015, 2016 English translation) depict the individual's search for the self at a specific historical moment of modern Turkey, problematizing the past, present, and future of the nation-state.
Keywords: Turkish Literature; World Literature; Istanbul; Ahmet Hamdi Tanpınar; Orhan Pamuk; Burhan Sönmez